2019
DOI: 10.25304/rlt.v27.2239
|View full text |Cite
|
Sign up to set email alerts
|

The effect of writing modality on recollection in children and adolescents

Abstract: We set out to assess the extent to which writing modality affects recollection in children and adolescents. We examined 10-to 11-year-old children's (N = 63) and 16-year-old adolescents' (N = 43) handwriting, keyboarding with a laptop computer and keyboarding with a touchscreen tablet computer or mobile phone in a within-subjects experimental design. Participants were instructed to write down stories dictated to them in the three writing modalities. Recollection of the stories was assessed using free recall of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…While the participants generally preferred to write with a keyboard on the computer, only one participant said that he preferred to write with a pen and paper. This was in line with the results of Frangou et al (2019), Mangen et al (2015) and Özdemir (2021). The participants stated that they used an online dictionary while writing the text, but they only translated words, not sentences and paragraphs.…”
Section: Discussionsupporting
confidence: 92%
“…While the participants generally preferred to write with a keyboard on the computer, only one participant said that he preferred to write with a pen and paper. This was in line with the results of Frangou et al (2019), Mangen et al (2015) and Özdemir (2021). The participants stated that they used an online dictionary while writing the text, but they only translated words, not sentences and paragraphs.…”
Section: Discussionsupporting
confidence: 92%
“…They rationalized it, stating they were more familiar with touch screens due to frequent texting. Mangen et al (2015) and Frangou et al (2019) stated that the contribution of touchpads to certain cognitive skills is correlated with experience. However, this study revealed that hand-writing was found most beneficial over keyboard and touch-screen.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Las estrategias de escritura a mano, el uso del teclado en una computadora portátil y el uso del teclado en una tableta con pantalla táctil o en un teléfono móvil afecta el recuerdo, mientras que la escritura a mano conduce a un mejor recuerdo. Sin embargo, actualmente, las herramientas de escritura digital están inundando las aulas y los lugares de trabajo de todo el mundo, lo que hace que su uso competente sea una necesidad en el mundo actual (S. Frangou et al ,2019). En ese sentido se requiere de evaluaciones de alfabetización temprana para que pueden identificar a niños que experimentan dificultades en la escritura, además de desafíos en la lectura temprana.…”
Section: B Estrategias De Desarrollo De La Escritura En Niñosunclassified